Comprehensive Physiology 2011
DOI: 10.1002/cphy.c100053
|View full text |Cite
|
Sign up to set email alerts
|

The Kallikrein‐Kinin System as a Regulator of Cardiovascular and Renal Function

Abstract: Autocrine, paracrine, endocrine, and neuroendocrine hormonal systems help regulate cardiovascular and renal function. Any change in the balance among these systems may result in hypertension and target organ damage, whether the cause is genetic, environmental or a combination of the two. Endocrine and neuroendocrine vasopressor hormones such as the renin-angiotensin system (RAS), aldosterone, and catecholamines are important for regulation of blood pressure and pathogenesis of hypertension and target organ dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 300 publications
(335 reference statements)
1
77
0
2
Order By: Relevance
“…Multiple reports are consistent with the notion that renal KKS promotes diuresis and natriuresis largely due to inhibition of tubular reabsorption of water and sodium (de Souza et al, 2013;Mukai, Fitzgibbon, Bozeman, Margolius, & Ploth, 1996;Rhaleb, Yang, & Carretero, 2011;Siragy, 1993;Sivritas et al, 2008;Suzuki, Katori, Fujita, Kumagai, & Majima, 2000). It appears that these effects occur in the absence of changes in glomerular filtration rate and renal blood flow (Siragy, 1993;Sivritas et al, 2008).…”
Section: Regulation Of Distal Nephron Sodium Reabsorption By Bk: a Romentioning
confidence: 63%
See 1 more Smart Citation
“…Multiple reports are consistent with the notion that renal KKS promotes diuresis and natriuresis largely due to inhibition of tubular reabsorption of water and sodium (de Souza et al, 2013;Mukai, Fitzgibbon, Bozeman, Margolius, & Ploth, 1996;Rhaleb, Yang, & Carretero, 2011;Siragy, 1993;Sivritas et al, 2008;Suzuki, Katori, Fujita, Kumagai, & Majima, 2000). It appears that these effects occur in the absence of changes in glomerular filtration rate and renal blood flow (Siragy, 1993;Sivritas et al, 2008).…”
Section: Regulation Of Distal Nephron Sodium Reabsorption By Bk: a Romentioning
confidence: 63%
“…It appears that these effects occur in the absence of changes in glomerular filtration rate and renal blood flow (Siragy, 1993;Sivritas et al, 2008). However, the evidence about a role of KKS in promoting vasodilation of renal vasculature also exists (Rhaleb et al, 2011). Taking into consideration the topology of renal KKS expression, it is suggested that inhibition of distal nephron water-electrolyte transport underlies the effects of kinins on renal function (Kauker & Nasjletti, 1986;Mukai et al, 1996;Zeidel, Jabs, Kikeri, & Silva, 1990).…”
Section: Regulation Of Distal Nephron Sodium Reabsorption By Bk: a Romentioning
confidence: 96%
“…During activation of innate immunity, PK in local tissue plays a promoting role through activation of C3 (Oikonomopoulou et al 2013). Through binding to B2R, BK can induce maturation of dendrite cells (DC) and release of interleukin (IL)-12 (Rhaleb et al 2011). Kinin receptor profile may, thus, change in a variety of pathological conditions (Zelawski et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…All these provide compelling evidence for a significant role of the KKS in TCEinduced sensitization and associated kidney injury. In the past few decades, accumulating evidence has established that the KKS contributes to the pathogenesis of inflammation (Rhaleb et al 2011). However, its role in inflammation generated by environmental chemicals via sensitization was little studied.…”
Section: Discussionmentioning
confidence: 99%
“…In myocardial infarction produced by ischemia/reperfusion, kinins help reduce infarct size following preconditioning or treatment with angiotensin-converting enzyme (ACE) inhibitors (Rhaleb, Yang, & Carretero, 2011). Kinins act via nitric oxide (NO) contribute to the vascular protective effect of ACE inhibitors during neointima formation, and kallikrein/kinin leads to increased levels and Akt activation, and reduces reactive oxygen species formation, TGF-beta1 expression, MAPK, and nuclear factor-kappa B activation (Chao & Chao, 2005).…”
Section: Efficacy and Safety Of Hukmentioning
confidence: 99%